Pojęcie energii i jego konsekwencje w psychoterapii - Szałek, Piotr (Acta Universitatis Lodziensis. Folia Philosophica. Ethica-Aesthetica-Practica, 2005)
Development of notion of energy resulted in appearing different interpretations in fields of physics and psychology. To psychology this concept was introduced by Mesmer. He believed that an influence of a physically perceptible fluid is the essence of therapeutic action. It was Freud who reformulated Mesmer's theory explaining that this influence should be understood as a transference. At the same time, the 19th century disputes between vitalism and mechanistic school of physiology brought a widespread consensus about the unity of all types of energy. This consensus led later to a gradual elimination of the concept of energy from psychology. In the 20th century interpretation of notion libido caused that idea of a specific vital energy returned in Reich's pieces. It is important that Reich was one of the most prominent psychotherapists of the 20th century. He created contemporary Bioenergetic Therapy. Representatives of this kind of therapy claim today that a notion of energy announces a rise of a new paradigm in science. Actually this notion creates a danger of introducing activities independent of any rational valuation into a field of healing procedures.